Transvaginal sonography with vs without bowel preparation in diagnosis of rectosigmoid endometriosis: prospective study. (6th February 2019) - Ferrero, S.; Scala, C.; Stabilini, C.; Vellone, V. G.; Barra, F.; Leone Roberti Maggiore, U.
ABSTRACT: Objectives: The primary aim of this study was to compare the diagnostic accuracy of transvaginal sonography (TVS) with vs without bowel preparation (BP) in detecting the presence of rectosigmoid endometriosis. Secondary objectives were to compare the diagnostic accuracy of the two techniques in estimating infiltration of the submucosa, length of the largest rectosigmoid nodules, distance of the nodules from the anal verge and presence of multifocal disease. Methods: This was a prospective study of patients with symptoms of pelvic pain for more than 6 months and/or suspicion of endometriosis referred to our institution between October 2016 and April 2018. Participants underwent a first TVS without BP followed by TVS with BP within a time interval of 1 week to 3 months. The examinations were performed independently and blindly by two sonographers. Only patients who underwent laparoscopy within the 6 months following the second ultrasound examination were included. Ultrasound results using the two techniques were compared with surgical and histological findings. Results: Of the 262 patients included in the study, 118 had rectosigmoid endometriosis confirmed at surgery. There was no significant difference in accuracy between TVS with and that without BP in diagnosing the presence of rectosigmoid endometriosis (93.5% vs 92.3%; P = 0.453). No significant difference was observed in accuracy between TVS with and that without BP in diagnosing submucosal infiltration (88.8% vs 84.6%; P = 0.238) and multifocal disease (97.2% vs 95.2%; P = 0.727) in patients diagnosed sonographically with rectosigmoid endometriosis. The accuracy of TVS with BP was similar to that of TVS without BP in estimating the maximum diameter of the largest nodule ( P = 0.644) and the distance between the more caudal rectosigmoid nodule and the anal verge ( P = 0.162). Conclusion: BP does not improve the diagnostic performance of TVS in detecting rectosigmoid endometriosis and in assessing characteristics of endometriotic nodules. Copyright © 2018 ISUOG. Published by John Wiley & Sons Ltd.